Potential Health Benefits From Downhill Skiing - Burtscher, Martin; Federolf, Peter A.; Nachbauer, Werner; Kopp, Martin (Frontiers in Physiology, 2019)
Objectives Downhill skiing represents one of the most popular winter sports worldwide. Whereas a plethora of studies dealt with the risk of injury and death associated with downhill skiing, data on its favorable health effects are scarce. A more comprehensive overview on such effects might emerge from a multidisciplinary perspective. Methods A literature search has been performed to identify original articles on downhill/alpine skiing interventions or questionnaire-based evaluation of skiing effects and the assessment of health effects (cardiorespiratory, neurophysiological, musculoskeletal, psycho-social). Results and Discussion A total of 21 original articles dealing with potentially favourable health effects resulting from downhill skiing were included in this review. Results indicate that downhill skiing, especially when performed on a regular basis, may contribute to healthy aging by its association with a healthier life style including higher levels of physical activity. Several other mechanisms suggest further favorable health effects of downhill skiing in response to specific challenges and adaptations in the musculo-skeletal and postural control systems, to exposures to cold temperatures and intermittent hypoxia, and/or emotional and social benefits from outdoor recreation. However, reliable data corroborating these mechanisms is scarce.